THE NEED FOR DISCOVERY LEARNING-BASED STUDENT WORKSHEETS (LKPD) TO IMPROVE STUDENTS’ LEARNING OUTCOMES AT ELEMENTARY SCHOOLS - Budi Sayekti; Murtono; A Hilal Madjdi (Jurnal PAJAR (Pendidikan dan Pengajaran), 2020)
This study aimed to describe the needs for Discovery Learning-based student worksheet (LKPD), especially for grade V SD Negeri Sukoharjo 01and 03, to improve students’ learning outcomes. This research was a development research utilizing Borg and Gall model which included seven steps, namely potentials and problems, data collection, product design, validation of design, revision of design, product testing, and product revision. The needs analysis of LKPD was conducted based on teachers’ and students’ perceptions to 50 students in the experimental class and 40 students in the control class. The data were collected through a questionnaire of material needs and a test for students’ learning outcomes. The results of the needs analysis based on the students’ and teachers’ perceptions included four aspects, namely (1) book content (89.1%), (2) language (91.25%), (3) presentation (88.9%), and (4) graphics (95.2%). The gain test ndicated an increase in students’ learning outcomes as much as 1.44 with high criteria from the cognitive aspects. Furthermore, the results of T test for the cognitive aspect was 0.172> 0.05 and T test for the psychomotor aspect was 0.062. Based on this result, there were differences in the learning outcomes between the experimental class and the control class. Thus, it could be concluded that Discovery Learning-based LKPD improved student learning outcomes